ENVIRONMENTAL PROBLEMS OF AGRICULTURAL LAND MANAGEMENT IN THE NORTH CAUCASIAN FEDERAL DISTRICT - M. R. Musayev; D. A. Shapovalov; V. A. Shirokova; P. V. Klyushin; A. O. Khutorova; S. V. Savinova (Юг России: экология, развитие)
Aim. The aim is to assess the environmental problems in the North Caucasus Federal District of the Russian Federation. Methods. An analysis of the literature and own research at a high anthropogenic pressure on agricultural land through the development of more stringent criteria for assessing the already degraded areas. Results. In the Stavropol region, Andropov district is in the most catastrophic state: of eight ratings five have the highest (fifth catastrophic degree) degree of degradation; two the first (low) and one rating has the second (middle). On the territory of Kabardino-Balkarian Republic, the highest degree of degradation of agricultural land is assigned to rocky ground, where it has a catastrophic rate of 9.76 points. For agricultural workers on steppe plains, the priority is to fight against deflation, as there is also a high degradation level 6.67 (above catastrophic). Conclusion. It was established that in the North Caucasus Federal District the system of rational use of land should be of environmental and resource-conserving nature and provide for the preservation of the soil, limiting the impact on flora and fauna, geological formations, and other components of the environment.